2016
DOI: 10.1177/1076029615627340
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Lymphocyte-to-Monocyte Ratio and Bare-Metal Stent In-Stent Restenosis in Patients With Stable Coronary Artery Disease

Abstract: In-stent restenosis (ISR) is a common clinical problem in patients with coronary artery disease treated with percutaneous coronary intervention. Inflammatory process plays a pivotal role in the development of ISR. Both lymphocytes and monocytes are associated with inflammatory status. Recently, it has been shown that the lymphocyte-to-monocyte ratio (LMR) is a novel inflammatory marker. We aimed to investigate the association of serum LMR levels and ISR in patients undergoing bare-metal stent (BMS) implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…[ 27 ] In another recent study, the relationship between LMR and bare-metal in-stent restenosis in patients with SCAD was reported. [ 28 ] This study supports that LMR, as an inflammatory biomarker, contributes to the development of atherosclerosis from initiation through progression. More recently, Ji et al found that monocyte to lymphocyte ratio predicts the severity of CAD by a syntax score assessment.…”
Section: Discussionsupporting
confidence: 76%
“…[ 27 ] In another recent study, the relationship between LMR and bare-metal in-stent restenosis in patients with SCAD was reported. [ 28 ] This study supports that LMR, as an inflammatory biomarker, contributes to the development of atherosclerosis from initiation through progression. More recently, Ji et al found that monocyte to lymphocyte ratio predicts the severity of CAD by a syntax score assessment.…”
Section: Discussionsupporting
confidence: 76%
“…[ 6 , 7 ] In addition, lymphocyte-to-monocyte ratio (LMR) has been recently studied that it was a novel marker of inflammation related to coronary artery disease. [ 8 ] Major adverse cardiac and cerebrovascular events (MACCE), which comprise stroke/transient ischemic attack (TIA), target vessel revascularization (TVR), nonfatal MI, and cardiovascular mortality, are very important adverse events associated with prognosis in patients with MI. In this study, we evaluated the relations between LMR and in-hospital and long-term MACCE in STEMI patients who underwent primary PCI to assess the prognostic value of LMR for STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Recently, the neutrophil-to-lymphocyte ratio, platelet-tolymphocyte ratio, and lymphocyte-to-monocyte ratio have been used as independent predictors of in-stent restenosis. [9][10][11] However, Celik et al 1 did not evaluate the combinations of these easily calculated inflammatory markers. Furthermore, they did not indicate which confounding factors were tested in the multivariate regression model.…”
Section: Celik Et Al 1 In Their Paper Entitled ''Preprocedural Albumimentioning
confidence: 99%